Urgent audiovisual relaxation training as a tool for managing stress reactions in first-year students - Nedovesova, S.A.; Kapustina, V.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to theoretically substantiate and experimentally verify methods of self-regulation among 1st-year students. Methods and structure of the study. 1st-year psychology students (n=32) participated in the scientific work during the winter session. Using the BOSLAB hardware and software complex, dynamic changes in key physiological indicators were recorded: skin galvanic response (SGR), photoplethysmogram (PPG), respiratory cycle duration, and exhalation duration. Results and conclusions. The phased nature of the adaptation processes was identified: an initial decrease in SGR (from 7.31±0.51 to 6.61±0.48 μS) followed by stabilisation (7.02±0.46 μS), wave-like dynamics of PPG (peak 307.31±29.75 u.e. in the first minute) and a significant increase in the duration of exhalation (from 1.48±0.07 to 1.89±0.16 s). The data obtained indicate a pronounced influence of psychophysiological reactions on vegetative regulation, especially on respiratory function, which confirms its effectiveness as a tool for managing stress reactions in an educational environment. The results of the study are of practical importance for the development of psychological support programmes for students during the period of adaptation to the academic workload.